Construction cluster innovation - Payne, David; Sarvaranta, Leena (International Journal of Strategic Property Management, 2010)
“Construction cluster innovation” International Journal of Strategic Property Management, 9(2), p. 53-54. First Published Online: 18 Oct 2010